Learning from people with dementia to improve accessibility of website interfaces - Savitch, Nada; Zaphiris, Panayiotis; Clare, Linda; Freeman, Ed (My University, 2004)
Computers could play an important part in improving the quality of life for people with dementia: for information seeking, communication and leisure. Computers and the Internet offer a special tool that could help people to maintain and learn new skills, develop hobbies and communicate with others in new ways. However, the design of interfaces often acts as a barrier to people with cognitive difficulties. Computer applications have been developed as tools in the diagnosis of dementia and the potential for using computers for activities in care settings is being recognised. However, very little research has been done into what people with dementia themselves need from computer interface design. This poster explores the attitude of people with dementia towards computers and the feasibility of involving them in the development of website design.
Keywords: Dementia; Disability; Distributed participatory design; Often passive consumers